Practical Resistance of Ostrinia nubilalis (Lepidoptera: Crambidae) to Cry1F Bacillus thuringiensis maize discovered in Nova Scotia, Canada - Smith, Jocelyn L. (Sci Rep, 2019)
Transgenic maize, Zea mays L., modified to express insecticidal proteins from the bacterium Bacillus thuringiensis Berliner, was introduced in 1996 to control Ostrinia nubilalis Hübner (Lepidoptera: Crambidae), a key maize pest in North America. The high-dose/refuge concept, developed to delay or prevent resistance evolution to this technology, has been exemplified by O. nubilalis as no cases of practical resistance were identified in >20 years. This study documents the first case of practical resistance to Cry1F Bt maize by O. nubilalis in North America. Four collections of O. nubilalis were made from Cry1F maize in Nova Scotia, Canada with unexpected injury (UXI) ranging from 30–70%. Greater survival of UXI collections was observed when larvae were exposed to the highest concentration of 200 ng Cry1F cm(−2) in diet-overlay bioassays compared to susceptible laboratory colonies. Larvae also fed and survived on Cry1F leaf tissue in 7 d bioassays. A collection from non-Bt maize, 120 km west of the UXI region, also survived 200 ng Cry1F cm(−2), but was susceptible to Cry1F leaf tissue. Detection of Cry1F-resistant O. nubilalis in what might be considered an insignificant maize-growing region indicates that a number of preventable causal factors may have been related to inadequate stewardship of Bt maize technology.